Improving How Caregivers of People Living With Dementia Are Identified in the Electronic Health Record: Qualitative Study and Exploratory Chart Review - Ariel R Green; Cynthia M Boyd; Rosalphie Quiles Rosado; Andrea E Daddato; Kathy S Gleason; Tobie E Taylor McPhail; Marcela D Blinka; Nancy L Schoenborn; Jennifer L Wolff; Elizabeth A Bayliss; Rebecca S Boxer (JMIR Aging)
Abstract BackgroundFamily and unpaid caregivers play a crucial role in supporting people living with dementia; yet, they are not systematically identified and documented by health systems. ObjectiveThe aims of the study are to determine the extent to which caregivers are currently identified and documented in the electronic health record (EHR) and to elicit the perspectives of caregivers and clinical staff on how to best identify, engage, and support caregivers of people living with dementia through the EHR. MethodsPeople with dementia were identified based on International Classification of Diseases, Tenth RevisionICD-10 ResultsCaregivers of people with dementia (N=22) were usually identified in the “contact information” or “patient contacts” tab (n=20, 91%) by their name and relation to the people with dementia; this tab did not specify the caregiver’s role. Caregivers were also mentioned, and their roles were described to a varying degree in clinical notes (n=21, 96%). Of the 22 caregivers interviewed, the majority (n=17, 77%) reported that the people with dementia had additional caregivers. The presence of multiple caregivers could be gleaned from most charts (n=16, 73%); however, this information was not captured systematically, and caregivers’ individual contributions were not explicitly recorded. Interviews with 22 caregivers and 16 clinical staff revealed two major themes: (1) caregiving arrangements are complex and not systematically captured or easy to locate in the EHR and (2) health systems should develop standardized processes to obtain and document caregiver information in the EHR. ConclusionsThis exploratory chart review and qualitative interview study found that people with dementia frequently have multiple caregivers, whose roles and needs are captured inconsistently in the EHR. To address this concern, caregivers and clinical staff suggested that health systems should develop and test workflows to identify caregivers, assess their needs at multiple touchpoints, and record their information in extractable EHR fields.